138 Cell-specific role of NOX2 NADPH oxidase in development of angiotensin ii-induced cardiac fibrosis in vivo. (9th June 2011) - Chaubey, S; Murdoch, C E; Ivetic, A; Yu, B; Vanhoutte, D; Heymans, S; Brewer, A; Shah, A M
Abstract : Introduction: Mice globally deficient in Nox2 are protected against cardiac fibrosis in response to chronic AngII infusion even though the degree of hypertrophy was unaltered. The selective effect of Nox2 on fibrosis may reflect its activation in a non-cardiomyocyte cell type. We hypothesised that Nox2, which is expressed in endothelial cells and inflammatory cells, may be important for cardiac fibrosis in these cell types. Methods: To investigate the role of Nox2 in inflammatory cells, we generated chimeric mice by irradiation (10Gy, 15 min) to deplete resident bone marrow cells, followed by bone marrow (BM) transplantation, using the following permutations: wild-type (WT) recipient with either KO or WT BM, and KO recipients with WT BM. To assess the role of endothelial Nox2, we used transgenic mice with endothelial-specific overexpression of Nox2 (TG) utilising the tie2 promoter construct. Result: AngII (1.1 mg/kg/day, 14-day) infusion caused similar increase in systolic hypertension and cardiac hypertrophy in all 3 chimeric groups. However, cardiac fibrosis assessed by Sirius red staining was significantly lower in KO mice receiving WT BM (0.5±0.1%) compared to the WT:WT group (2.7±0.7%) or in WT receiving KO BM (2.3±0.6%). These data suggested that resident Nox2-expressing cells are responsible for the protective effect observed in global Nox2 KO mice. TG mice developed the same level of systolic hypertension and hypertrophy as WT littermates after AngII infusion. However, the extent of cardiac fibrosis was significantly greater in TG than WT by ∼2-fold (p<0.05). This was associated with a greater degree of infiltration by CD45+ inflammatory cells (∼1.8-fold, p<0.05) and 30% (p<0.05) more VCAM-1 positive blood vessels in AngII treated TG hearts. Furthermore, isolated TG endothelial cells recruited ∼2-fold (p<0.05) more leukocytes than WT upon AngII treatment. Conclusion: These results indicate there is a cell-specific role of endothelial Nox2 in the development of fibrosis. Endothelial Nox2 enhances AngII-induced cardiac fibrosis, possibly by enhancing inflammatory cell recruitment and influx via VCAM-1 expression. Although inflammatory cells may be important for the development of fibrosis, our results indicate that Nox2 in these cells is not essential for any pro-fibrotic effect.